Mengungkap Peran Mental Accounting dalam Pengelolaan Keuangan Geprek Generation - Melia, Melia; Yantiana, Nella (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study aims to understand how mental accounting plays a role in the financial management of geprek generation who have limited finances but have dependents in the family and how social pressure affects this. This research applies a qualitative method with a phenomenological approach through in-depth interviews. The condition of the geprek generation requires individuals to be wiser in managing their finances but the development of the digital world with flexing content can be an influence on personal financial planning. The results showed that in financial management by the geprek generation, there is a mental accounting process as a self-control on their decisions. In addition, the mental accounting process occurs in the allocation of finances assigned to certain account items such as decisions on self rewarding decisions. With the application of mental accounting, there is a better decision-making process in financial management.